The “Third Hand”: IT-Enabled Competitive Advantage in Turbulence Through Improvisational Capabilities - Pavlou, Paul A.; El Sawy, Omar A. (Information Systems Research, 2010)
Organizations are increasingly engaged in competitive dynamics that are enabled or induced by information technology (IT). A key competitive dynamics question for many organizations is how to build a competitive advantage in turbulence with digital IT systems. The literature has focused mostly on developing and exercising dynamic capabilities for planned reconfiguration of existing operational capabilities in fairly stable environments with patterned “waves,” but this may not always be possible, or even appropriate, in highly turbulent environments with unexpected “storms.” We introduce improvisational capabilities as an alternative means for managing highly turbulent environments; we define this as the ability to spontaneously reconfigure existing resources to build new operational capabilities to address urgent, unpredictable, and novel environmental situations. In contrast to the planned role of dynamic and operational capabilities and the ambidexterity that they jointly offer, improvisational capabilities are proposed to operate distinctly as a “third hand” that facilitates reconfiguration and change in highly turbulent environments. First, the paper develops the notion of improvisational capabilities and articulates the key differences between the two “reconfiguration”—improvisational and dynamic—capabilities. Second, the paper compares the relative effects of improvisational and dynamic capabilities in the context of new product development in different levels of environmental turbulence. Third, the paper shows how IT-leveraging capability in new product development is decomposed into its three digital IT systems: project and resource management systems, organizational memory systems (OMS), and cooperative work systems—and how each of these IT systems enhances improvisational capabilities, an effect that is accentuated in highly turbulent environments. The results show that although dynamic capabilities are the primary predictor of competitive advantage in moderately turbulent environments, improvisational capabilities fully dominate in highly turbulent environments. Besides discriminant validity, the distinction between improvisational and dynamic capabilities is evidenced by the differential effects of IT-leveraging capability on improvisational and dynamic capabilities. The results show that the more the IT-leveraging capability is catered toward managing resources (through project and resource management systems) and team collaboration (through cooperative work systems) rather than relying on past knowledge and procedures (through organizational memory systems), the more it is positively associated with improvisational capabilities, particularly in more turbulent environments. The paper draws implications for how different IT systems can influence improvisational capabilities and competitive advantage in turbulent environments, thereby enhancing our understanding of the role of IT systems on reconfiguration capabilities. The paper discusses the theoretical and practical implications of building and exercising the “third hand” of improvisational capabilities for IT-enabled competitive dynamics in turbulence.